2001
DOI: 10.4269/ajtmh.2001.65.366
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the peripheral immune response in patients with neurocysticercosis: evidence for T cell reactivity to parasite glycoprotein and vesicular fluid antigens.

Abstract: Abstract. In neurocysticercosis (NCC), it is thought that the long-term survival of the parasite within the human brain is due in part to the ability of the cestode to suppress the local immune response. When the parasite dies, the immunosuppression is apparently lost and a strong local inflammatory response then develops. In contrast, little is known about the immunologic response that may occur in the peripheral immune system of these patients. In this study, the status of the peripheral (extracerebral) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This study focused on specimens that had a granuloma surrounding brain cysticerci. Despite the previously documented heterogeneity of cellular and humoral immune responses among patients with NCC, in the present study a consistent in situ response was observed in eight cases where granulomas surrounded brain cysticerci (21,28,29). Essentially, each specimen contained a dead and disintegrating parasite that was surrounded by an immune granuloma with intense fibrosis, inflammation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…This study focused on specimens that had a granuloma surrounding brain cysticerci. Despite the previously documented heterogeneity of cellular and humoral immune responses among patients with NCC, in the present study a consistent in situ response was observed in eight cases where granulomas surrounded brain cysticerci (21,28,29). Essentially, each specimen contained a dead and disintegrating parasite that was surrounded by an immune granuloma with intense fibrosis, inflammation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, genetic, immunological, and hormonal factors have been related to resistance in this model (14,15,20,22,31,41). Likewise, some of these observations have been confirmed in the natural hosts for T. solium (30,33,34).…”
mentioning
confidence: 68%
“…Considering the relevance of neuroinXammation in NC pathogenesis, increased eVorts have been performed to characterize the immune-inXammatory response in NC and its role in dealing with the parasite [9][10][11][12][13][14][15][16][17]. All studies have been performed studying the CSF (local) or blood (peripheral) of NC patients independently.…”
Section: Introductionmentioning
confidence: 99%